Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.inorgchem.0c02137
|View full text |Cite
|
Sign up to set email alerts
|

Os(II) Oligothienyl Complexes as a Hypoxia-Active Photosensitizer Class for Photodynamic Therapy

Abstract: Hypoxia presents a challenge to anticancer therapy, reducing the efficacy of many available treatments. Photodynamic therapy is particularly susceptible to hypoxia, given that its mechanism relies on oxygen. Herein, we introduce two new osmium-based polypyridyl photosensitizers that are active in hypoxia. The lead compounds emerged from a systematic study of two Os­(II) polypyridyl families derived from 2,2′-bipyridine (bpy) or 4,4′-dimethyl-2,2′-bipyridine (dmb) as coligands combined with imidazo­[4,5-f]­[1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 77 publications
8
72
0
Order By: Relevance
“…This result is consistent with other recent findings by our group that demonstrate that seemingly innocuous structural changes can have a very significant influence on a compound’s photocytotoxicity in normoxia and in hypoxia (28,29). The present study not only validates the findings from our previous report regarding the activity of 1 and the inactivity of 5 , but it explores in greater depth the apparent dichotomy of these two NIP isomers.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is consistent with other recent findings by our group that demonstrate that seemingly innocuous structural changes can have a very significant influence on a compound’s photocytotoxicity in normoxia and in hypoxia (28,29). The present study not only validates the findings from our previous report regarding the activity of 1 and the inactivity of 5 , but it explores in greater depth the apparent dichotomy of these two NIP isomers.…”
Section: Introductionsupporting
confidence: 93%
“…Since they were designed as PCT agents for low‐oxygen conditions, the compounds were evaluated in hypoxia (1% O 2 ) using a protocol similar to the normoxic screen but with hypoxia maintained up to and during the light treatment. Our standard hypoxia assay protocol (28–30) involves preincubating the cells under hypoxic conditions prior to compound addition, applying a film over the well plates before removal from the hypoxia chamber for light treatment outside the hypoxic chamber, and incubating the cells in normoxia after irradiation (since the resazurin cell viability assay used for quantifying live versus dead cells is based on metabolic respiration). We have confirmed that this is a robust method for testing photocytotoxicity in hypoxia (28–30), and provides low oxygen tension at the time of illumination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TA spectra change substantially for Ru‐ip‐2T through Ru‐ip‐4T , which have very strong and much more structured excited state absorptions with maxima at 550, 630, and 680 nm, respectively. This systematic red‐shift of the excited state absorption with increasing n , by over 100 nm, is characteristic of oligothiophene‐based 3 IL states [5,17] . Thus, the ns TA spectra indicate that the character of the long‐lived state changes from 3 MLCT for Ru‐ip‐0T and Ru‐ip‐1T to predominantly 3 IL with additional thiophene rings.…”
Section: Figurementioning
confidence: 87%
“…This band corresponds to the ππ* 1 IL transition associated with the oligothiophene [16] . These oligothiophene‐localized transitions have been computed to have substantial charge transfer character and are best described as intraligand charge transfer (ILCT) states, but are referred to herein more generally as IL [17,18] …”
Section: Figurementioning
confidence: 99%